India and Israel: A New Era of Relations - GOGOI, SUSMITA (Journal of Advanced Research in Humanities and Social Sciences, 2022)
India and Israel both share similar ideological and cultural bond in the 21st century but India had not recognize Israel as a state till 1950 and today it has been more than 30 years of diplomatic ties with growing economic, defense and strategic relationship. Diplomatic relations formally developed between the two after the opening of Israeli embassy in India in 1992. After the establishment of formal diplomatic relations, the relations between the two countries started gaining firmness in 1996 and 1998 onwards. In 1999 Kargil Confrontations, unconditional help was provided to India by Israel (to gather intelligence and military support). Relations between the two democratic nations further intensified with the visits of the two Heads of governments. Prime Minister Narendra Modi was the first Prime Minister of India to visit Israel in 2017 and Prime Minister Benjamin Netanyahu to India in 2018. How to cite this article:  Gogoi S. India and Israel: A New Era of Relations. J Adv Res Humani Social Sci 2022; 9(4): 26-30.